Kaji Ekperimental Karakteristik Pengeringan Ikan Bandeng Pada Alat Pengering Berbahan Bakar Gas - Muhammad Thaib Hasan; Ahmad Syuhada; - Hamdani (Jurnal Teknik Mesin Unsyiah, 2012)
Aceh is one of the biggest milkfish (chanos-chanos Forsskal)-producing provinces in Indonesia and the production is increasing year by year. However, beyond that prospect, there are disadvantages of the milkfish which are able to be putrid easily and are not able to be kept for a long time. In addition, at the time of great harvest and the fish production is plenitude and less of the fish is in use that the price of the fish decreases sharply. The population of Aceh generally like to consume fresh and dried milkfish especially the people in the rural and highland. Based on the result of the previous research, the drying method which is done by putting the fish under direct sunlight is inefective as the sunlight is not perpetually present as expected. Even the quality of the product is low as the fish is contaminated by flies. In addition it requires large drying areas to produce large quantity fish. In this research, it is conducted eksperimental analysis and drying characteristic of the milkfish in the drying process by using drying equipment with gas fuel. The drying equipment used is the shelf type which is located in Thermal Engineering Laboratory, Mechanical Engineering, Engineering Faculty, Syiah Kuala University. The equipment consists of burning room, drying room and chimney. The weight of  milkfish model is 200 grams, 250 grams, and 300 grams. Based on the test result on the milkfish weighted 200 grams after the drying process, it can be seen that the content of protein 18,97 %,fat 3,75%, water 19,20% with the total drying process of six hour.